The nature of the political system of Germany and their effect on foreign policy (The Syrian refugees as a model from 2011–2019) - Hassan, Sabir Adam; Ahmaday, Mohammed Diyaa Aldeen Mohammed; Khamis, Mogahid Abdallah (Journal of Humanities & Social Sciences, 2020)
This study highlighted the conditions of Syrian refugees in Germany And how to accommodate them in light of the difficult conditions that these refugees are exposed to, especially since many European countries refused to receive them, so we will know through this study to what extent Germany was able to contain these refugees in the light of its internal and external policies. The study relied on the descriptive analytical approach to analyze the impact of the nature of the German political system on foreign policy. The historical method was also used in the study to refer to some historical events that have significance in research events The study reached a number of results, the most important of which is a partial shift in German foreign policy through the adoption of more positive attitudes in dealing with international crises. The study also stressed that the stability of international and humanitarian conditions is the main objective of German foreign policy to ensure balanced international economic relations, In addition, the study concluded that the German state adopted a policy of holding the stick from the center towards the Middle East region in order to secure its economic interests with the Arab countries. Of the spread of the threat of terrorism in Europe and through the large migrations of Syrian refugees to Germany The study also reached a number of recommendations, the most important of which should be a partnership between the State of Germany and the organizations and institutions concerned with refugee affairs because they are more aware of the needs of refugees and this makes it easier for the government to take the right steps and effective decisions to help them. With the customs and traditions of the German society, it is also an important recommendation to find a political solution to the Syrian crisis with the participation of the various parties to the conflict under the auspices of European and international.